Effect of Bedding Orientation and Spatial Variability of Stratification Shear Strength on Stability of Transversely Isotropic Rock Slope - Zhou, Su-Hua; Zhou, Shuai-Kang; Zhang, Jiu-Chang; Tan, Xin (Frontiers in Physics, 2021)
The spatial variability of soil properties is inherent. A series of direct shear tests were carried out on strongly weathered slates samples with weak bedding planes, the result of which indicates the existence of variability of shear strength parameters. Based on the testing results, several numerical simulations of slopes were conducted considering such a variability of shear strength. The results had shown that the weak bedding planes affect the shape of sliding arc as well as the factor of safety of slopes. As the dip angle of bedding planes increases, the shape of the sliding surface changes from circular to a mixed form of circular and planner. When incorporating the spatial variability of weak planes’ shear strength into the stability analysis, the safety factors of slopes would reduce, in which the sliding arc exhibited a sliding band comprising multiple sets of sliding arcs.